Atypical Vaginal Aggressive Angiomyxoma in a Virgin: A Case Report from South Jordan - Al-Kharabsheh AM; AlTarawneh BK; Abufraijeh SM; Abu Azzam O (Dove Medical Press, 2024)
Ahlam M Al-Kharabsheh,1 Bushra Khalaf AlTarawneh,2 Seham M Abufraijeh,1 Omar Abu Azzam1 1Department of Obstetrics and Gynecology, Faculty of Medicine, Mutah University, Alkarak, Jordan; 2Department of Pathology, Faculty of Medicine, Mutah University, Alkarak, JordanCorrespondence: Ahlam M Al-Kharabsheh, Obstetrics and Gynecology department, Faculty of Medicine, Mutah University, Alkarak, Jordan, Tel +962-798009216, Email alkharabsheh@mutah.edu.joAbstract: Aggressive angiomyxoma is a locally invasive, rarely diagnosed mesenchymal tumor that predominantly affects the perineal region of women in their reproductive years. It is typically found in areas such as the vagina, vulva, and other pelvic soft tissues, but its presentation can be highly variable. We describe a particularly unique case of aggressive angiomyxoma, presenting in an atypical manner within the vaginal region of a 31-year-old virgin woman. This case is noteworthy for the unusual growth pattern of the angiomyxoma-located strictly within the vaginal epithelium, showing no signs of invasion into surrounding tissues, which is not typical of the aggressive nature of this type of tumor. The patient presented with a mass that protruded through the hymen, an uncommon presentation that led to initial speculation about the nature of the mass. The definitive diagnosis of aggressive angiomyxoma was made by meticulous histopathological examination after surgical excision of the mass. This case emphasizes the critical importance of considering aggressive angiomyxoma in the differential diagnosis of vaginal masses, particularly those that do not exhibit invasive characteristics. The case also highlights the need for increased awareness among clinicians about the potential for atypical presentations of this rare tumor, to facilitate timely and accurate diagnosis, and to guide appropriate management strategies. This report contributes to the growing body of literature on aggressive angiomyxoma, highlighting the variability in its presentation and the need to heighten suspicion in atypical cases.Keywords: aggressive angiomyxoma, vaginal cyst, vaginal tumor, mesenchymal tumor, case report